Medium- and High-Frequency Vibration Characteristics of a Box-Girder by the Waveguide Finite Element Method - Song, L.; Li, X.; Hao, Hong; Zhang, X. (World Scientific Publishing Co. Pte. Ltd., 2018)
© 2018 World Scientific Publishing Company An approach to predicting the vibration responses of a bridge and analyzing the wave propagation characteristics along the bridge is proposed based on the waveguide finite element (WFE) method. For verification, a field vibration test was performed on a 30(Formula presented.)m-long simply supported box-girder on the fourth line of Guangzhou Metro in China. The numerical results were shown to agree well with the test results, demonstrating the accuracy of the proposed approach. The advantages of the WFE approach are discussed by comparing the WFE with finite element (FE) analyses. The dispersion characteristics and mode shapes of waves propagating in the box-girder are calculated by using the WFE method, from which the dominant wave modes corresponding to the peaks of the medium- and high-frequency train-induced vibrations are identified. A vibration reduction measure is considered. Both the test and numerical results show that the medium- and high-frequency vibrations of the box-girder are predominately in the 1/3 octave center frequency range of 63–100(Formula presented.)Hz with maximum occurring at the center frequency of 80(Formula presented.)Hz. The WFE method has higher computational efficiency and requires smaller storage space than the FE counterpart, but provides similar predictions as the latter. In total, there are 14 wave modes propagating in the box-girder below 200(Formula presented.)Hz. The G1, A1 and D2 wave modes are the dominant wave modes generating vibration velocity peaks on the top, bottom and flange slabs, respectively. Adding a middle web slab to the center of the cross-section is an effective way to mitigate the vibration of the box-girder bridge.